Efficacy of HL036 versus Cyclosporine A in the Treatment of Naturally Occurring Canine Keratoconjunctivitis Sicca. (3rd July 2018) - Lee, Han-Byul; Choi, Hyun-Ji; Cho, Sung-Min; Kang, Suzie; Ahn, Hyea Kyung; Song, Yeon Jung; Kim, Young Ju; Son, Woo-Chan
ABSTRACT: Purposes : To (i) evaluate the efficacy and safety of HL036, a tumor-necrosis factor (TNF)-α-blocking protein, in the treatment of naturally occurring canine keratoconjunctivitis sicca (KCS) and (ii) compare these features with those of 1% cyclosporine A (CsA). Materials and Methods : Dogs ( n = 29) diagnosed with KCS were randomly assigned to receive one drop topical aqueous HL036 (0.2, 1, or 5 mg/mL) or 1% CsA in the affected eye(s) at 12-h intervals for 42 days. Schirmer's tear test (STT), fluorescein corneal staining (FCS), and clinical-sign scores were evaluated prior to application (day-0) and on days 14, 28, and 42 post-treatment. Of the 29 dogs enrolled, 19 (65.5%) received HL036 (HL036 group) and 10 (34.5%) received 1% CsA (CsA group). A linear mixed-effects model analysis was performed to determine score differences between groups and over time. Results : After treatment, clinical-sign scores and STT values had significantly improved compared with baseline levels in dogs of both treatment groups. Decreases in total clinical-sign scores for the HL036-group were greater than those of 1% CsA group. No severe adverse reactions were noted in either group. Conclusions : Our findings suggest that topical aqueous HL036 is well-tolerated and more effective than 1% CsA for treating naturally occurring canine KCS.